Character-Based Curriculum Management in Islamic Senior High Schools: A POAC Approach to Strengthening Student Character - Anis Choirun Niswah; Ainur Rifqi; Erny Roesminingsih; Amrozi Khumaidi (Journal of Educational Management Research, 2026)
This study aims to analyze the management of a character-based curriculum in an Islamic Senior High School using the Planning, Organizing, Actuating, and Controlling (POAC) management framework. A qualitative case study approach was employed to examine how character values are systematically integrated into the Independent Curriculum through curriculum planning, implementation, and evaluation. Data were collected from 20 participants, including teachers, vice principals, students, and parents, through in-depth interviews, participant observation, and document analysis. The data were analyzed using the interactive he support of NVivo 12. The findings indicate that character-based curriculum management was implemented effectively, achieving an overall effectiveness level of approximately 75%. Islamic values, including akhlakul karimah, discipline, and responsibility, were integrated through project-based learning, daily habituation, and pesantren-inspired activities. Nevertheless, the implementation faced challenges related to limited resources, insufficient teacher professional development, and the adaptation to post-pandemic hybrid learning. The study implies that continuous teacher training, digitalized character assessment systems, and stronger collaboration among school stakeholders are essential to enhance curriculum effectiveness and strengthen the Pancasila Student Profile with Rahmatan lil Alamin values.